Simulation of invasive ultrasonic tomography for three phase mixture - Alfareh A.; Rahiman M.H.F.; Talib M.T.M.; Pusppanathan J.; Juliza Jamaludin (Universiti Teknikal Malaysia Melaka, 2024)
Indexed by SCOPUS